Generasi Sandwich: Beban Pengasuhan dan Dukungan Sosial pada Wanita Bekerja - Fitri Ayu Kusumaningrum (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2018)
This study aims to find the relationship between social support and the caregiver burden for working women of sandwich generation. The hypothesis is tested based on the assumption that social support correlates with the caregiver burden. 108 female subjects working sandwich generation were selected in this study. Data was collected using a social support questionnaire based on the scale of the Multidimensional Scale of Perceived Social Support (MSPSS) developed by Zimet (1988) and parenting burden questionnaire based on the scale of Burden Scale for Family Caregivers (BSFC) developed by Gräsel, Chiu, Oliver (2003). The analysis of this study uses the Product Moment correlation by Pearson. The results of the analysis showed that there was a significant negative relationship between social support and caregiver burden p=0.000 (p <0.05) and r=0.172. The results showed that the higher the perception of social support, the lower the burden of care for respondents.